Are Wages in Southern Europe more Flexible? The Effects of a Cohort Size on European Earnings - Giorgio Brunello; Charlotte Lauer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
We exploit the cross?country and time variation in the demographics and education structure of 11 European countries to study how cohort size has affected real earnings in Europe. When we pool the data of all countries, we find that cohort size has a negative and statistically significant effect on the earnings of the older cohorts – aged between 35 and 54 – but no statistically significant effect on the earnings of younger cohorts – aged 20 to 34. The negative effect of cohort size on earnings is completely driven by Southern European countries, a result which we relate to institutional differences. While the share of 20-34 year-olds in the population has declined in the EU11 by 10.20 percent between 1991 and 2001, the share of 35-54 year-olds has increased by 9.32 percent. Our estimates suggest that, as a consequence of these significant demographic changes, the real earnings of the younger cohorts have increased on average by a tiny 0.06 percent, while the earnings of the older cohorts have declined by 0.93 percent, a modest variation.
Keywords: J31; J11; 330; cohort size; wages; Europe; Lohnstruktur; Kohortenanalyse; Alternde Bevölkerung; Lohnrigidität; Europa; Südeuropa